Hubungan Riwayat Perilaku Ibu Hamil Dengan Kejadian BBLR Di Kota Bontang - Sulastri, Rina; Kurniasari, Lia (STIKES Yayasan RS.Dr.Soetomo, 2022)
Maternal behavior during pregnancy can have an effect on how much the newborn. Knowledge, attitudes, and actions of pregnant women can be used to assess their behavior. The purpose of this study is to ascertain the connection between the history of pregnant women's behavior and the incidence of LBW in Bontang City. The method in this research is quantitative with Case Control design. Mother with babies age 6-12 months are the population of this study in the North Bontang Health Center area. The method of sampling used in this study case is using simple random sampling method, while the control sample is using a method of purposive sampling using a sample of 72 mothers. Data collection is by using questionnaires. The chi-square test is the statistical analysis method employed. The outcomes of the study obtained mother's knowledge with p-value = 0.336 (OR = 1.789; 95% CI = 0.690-4.641). Attitude variable obtained p-value = 0.016 (OR=3.750; 95% CI=1.379-10.200). Meanwhile, for the mother's action variable, p-value = 0.018 (OR=3.571; 95% CI=1.346-9.475) was obtained. According to the study's findings, there is a significant connection between the attitudes and actions of mothers with the incidence of LBW. Meanwhile, mother's knowledge has no relationship with the incidence of LBW.